Feitio de uma escrita por si em Maria Gabriela Llansol - Lima, Sueli Gomes de (2020)
Maria Gabriela Llansol, a ceaseless source of language in writing and thinking, is the one who chooses the word and decides what is real. Her traced characters are the study objective of this dissertation, entitled Feitio de uma escrita por si em Maria Gabriela Llansol (Writing Style of oneself writing by Maria Gabriela Llansol). The objective of this work is to propose a way of reading Llansol’s work, to reflect on the active force of her writing, which opens to language paths, that the so-called traditional literature was not able to show us. The pertinence and persistence of this writing force we named ‘Oneself writing’. It deals with a type of writing with stress in signs of experience that goes beyond the symbolic field, and, for this reason, has no representation. Our proposal is to set a kind of signifier that formulates an idea, a thought from the work of Maria Gabriela Llansol, based on the expression “Oneself writing.” Such work hypothesis is founded on the metalinguistic traces of her work. In other words, we aim to extract the thought about the process of composition of her writing, the project of writing her prose of poetic shades from her aesthetic and literary value. Our study is textualized as it follows: the presentation, when we place the text in the look of the general landscape of the Llansol universe. Chapter 1 introduces Llansol’s project and it is full of textuality, however, it has to do with a divergent conception of realistic aesthetic with verisimilitude value. In this trajectory, beyond a representative language, we have a special dialogue with Jacques Rancière (1995, 2005); Maurice Blanchot (2011a, 2011b); Jacques Derrida (2005, 2006); and Jorge Larrosa (2014). Based on Llansol’s critical-acclaim, we have selected studies by Lucia Castello Branco (2011, 1997a, 1997b, 1997c, 1997d); Cláudia Pedrosa Soares (2015) and Jorge Fernandes da Silveira (2013). Chapter 2 textualizes our reflections around the characteristics that resonate through our one writing in Llansol’s work. At this moment, we rely on Roland Barthes (1987, 1990, 2002, 2012); Eneida Maria de Souza (2002, 2011); Paul Zumthor (2014); and Michel Foucault (2007). Among Llansol’s expositors, we have a special dialogue with Silvina Rodrigues Lopes (2013); Vania Baeta Andrade (2006); Elisa Arreguy Maia (2013, 2012); Juliana Cabral Junqueira de Castro (2014); Cinara Araújo (2008) and Carlos Eduardo Batista Souza (2018). In chapter three, our interest is in the flow of the author’s writings that merges with words, text, language, work and book (become) and, for this reason, we base on Maria José Motta Viana (1995); João Barreto (2001, 2007a, 2007b, 2014c); Paulo Fonseca Andrade (2010, 2013); and Maria Carolina Junqueira Fenati (2015). In chapter four, Llansol’s theoretical field is related to the notions-concept executer for her oneself writing. In the conclusion, a writing anchored on the knowledge to be extracted from the text can be observed. In addition, in this grouping of words, this study considers the images of thought of several authors, such as César Guimarães (1997); Erick Gontijo Costa (2008, 2014); and José Augusto Mourão (2014). Finally, this dissertation requires us to write fast and soft about LLansol’s work, reflecting deeply on her thoughts - the one who was born to write and wrote to sur-vive.